Monitoring of destruction and shallowing of water bodies and bank protection structures in the Volga river delta within the framework of the "Ecology of safe construction" program - T. V. Zolina; S. P. Strelkov; N. V. Kupchikova; R. I. Shayakhmedov; K. G. Kondrashin (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The article describes the features of works on coastal protection of territories subject to slope processes. The role of research of leading processes of destruction of coastal zones in the framework of the program “The Ecology of Safe Construction and Municipal Services” for forecasting and preventing risks, as well as providing information for further work on building reliable coastal protection, is emphasized. Despite the existing variety of ways to protect embankments from erosion, the search for new technical solutions at the moment continues to be an urgent task.Methods. Geotechnical monitoring of hydraulic structures was carried out. Visual assessments of cracks, slopes of individual structural blocks, and deformations were performed. A thermal imager device is used to search for abnormal temperatures and an electronic hardness meter that measures the strength of concrete.Results. It is determined that the water regime of the Astrakhan Region is characterized by an uneven distribution of runoff due to a direct dependence on the flow rate from the Volgograd hydropower plant. The predominant source of moisture is discharges in the form of a series of rain floods, which often cause flooding. One of the most effective solutions is to preserve the operational characteristics of the bank protection spur-pile of variable cross-section when changing the hydrological river regime. The bank protection spur runs partially movable horizontally and vertically and comprises a head spur in the form of piles of variable height; the body in the form of a floating garland of variable cross-section; the base in the form of a slider block. The design and technological solution allow blocking the coastal stream with the body of the spur at any water level and changing the angle of inclination of the spur with the protected shore.Conclusion. Prevention of emergencies, especially in urbanized areas that are subject to intense anthropogenic impact, is possible only when engineering protective structures are built, which have a positive effect both in protective and environmental aspects.